Proposed Human Resource Competency for Society 5.0 - Lubis, Anggia Sari; Lubis, Abdul Rahman (Mimbar Ilmu, 2024)
Society 5.0 can also be interpreted as a concept of a human-centered and technology-based society. The competency model will support the effectiveness of the recruitment and selection process so that companies can attract the talents needed to build their HR performance. Thus, the development of a competency model for Society 5.0 has considerable value in terms of education, training, and human development perspectives in facing the era of change, especially Society 5.0. The purpose of this study is to conduct an in-depth analysis of existing research and practice competency models and continue the development of competency models for Society 5.0. The research method uses Systematic Literature Review (SLR) is a research method used to collect, review and synthesize relevant literature in a particular research field. A literature search was conducted through academic databases, such as PubMed, ERIC, and Google Scholar, using appropriate keywords such as “human resource competency”, “society 5.0”.  Next, this data is analyzed to identify patterns, trends, and consistencies in the findings. This study found that concepts of industrial revolution 4.0 and Society 5.0 focus on increasing the digitalization of the value chain, with humans as the main component in Society 5.0. To face the Society 5.0 era, human resources need to adapt to future challenges with high-level thinking abilities. Society 5.0 presents opportunities and challenges for companies. Human resource competency requires hard skills that are adapted to the Society 5.0 era.